The plant mitochondrial protein import apparatus — The differences make it interesting - Murcha, Monika W.; Wang, Yan; Narsai, Reena; Whelan, James (Biochimica et biophysica acta, 2014)
Mitochondria play essential roles in the life and death of almost all eukaryotic cells, ranging from single-celled to multi-cellular organisms that display tissue and developmental differentiation. As mitochondria only arose once in evolution, much can be learned from studying single celled model systems such as yeast and applying this knowledge to other organisms. However, two billion years of evolution have also resulted in substantial divergence in mitochondrial function between eukaryotic organisms. Here we review our current understanding of the mechanisms of mitochondrial protein import between plants and yeast (Saccharomyces cerevisiae) and identify a high level of conservation for the essential subunits of plant mitochondrial import apparatus. Furthermore, we investigate examples whereby divergence and acquisition of functions have arisen and highlight the emerging examples of interactions between the import apparatus and components of the respiratory chain. After more than three decades of research into the components and mechanisms of mitochondrial protein import of plants and yeast, the differences between these systems are examined. Specifically, expansions of the small gene families that encode the mitochondrial protein import apparatus in plants are detailed, and their essential role in seed viability is revealed. These findings point to the essential role of the inner mitochondrial protein translocases in Arabidopsis, establishing their necessity for seed viability and the crucial role of mitochondrial biogenesis during germination. This article is part of a Special Issue entitled Frontiers of Mitochondrial Research. [Display omitted] •Up to two billion years of evolution separate mitochondria from various groups.•Small gene families encode mitochondrial protein import components in plants.•Components of the import apparatus play role(s) in signalling and development.